Relationship Between Drinkers’ Motivation Before Therapy and Propensity to Relapse After Therapy Among Undergraduates with Substance Use Disorders in Nigerian University - Ajiboye, Samuel Adedotun; Mokuolu, Bolade Olubunmi; Olatunji, Samuel Olutunde (British Journal of Healthcare and Medical Research, 2023)
Relapse cases after alcohol use disorder treatments have been a great challenge to individuals suffering from addiction, their families, and mental health professionals. This study examined influence of drinkers' readiness to change on their propensity to relapse after therapies. It also examined other factors that could be responsible for propensity to relapse after therapies among undergraduates in Ekiti State University. 24 students, male (n=19) and female(n=5), who scored 7 and above in Alcohol Use Disorder Identification Test and showed interest in therapy during baseline survey and were randomly assigned into three treatment groups and one control group. Drinkers’ motivation was tested before therapy and while propensity to relapse was assessed after therapy. The research shows that all stages of drinkers’ motivation to change jointly predict propensity to relapse [F (3, 20) = 3.19, p = .046, R2 = .32]; meanwhile, only ambivalence (lack of motivation) significantly predict propensity to relapse [β=6.73, p = .006]. Propensity to relapse is significantly higher among male (mean = 100.89) than female (mean = 67.80); t(22) = 3.41, p<.01; meanwhile there is no significant sex difference in readiness to change among participants. It is clear from this study that lack of motivation among drinkers significantly predict higher propensity to relapse. In addition, gender related issues should be considered during therapies to prevent relapse. It is pertinent therefore, that therapists in Substance use disorder/addiction treatment centers should ensure drinkers’ motivation to quit alcohol use before therapies and conduct pretreatment assessment to identify individual factors that may engender relapse after therapies.